2018
DOI: 10.1523/eneuro.0153-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Intra-Habenular Activation of the Orphan G Protein-Coupled Receptor GPR139 Decreases Compulsive-Like Alcohol Drinking and Hyperalgesia in Alcohol-Dependent Rats

Abstract: GPR139 is an orphan G protein-coupled receptor (GPCR) that is expressed mainly in the brain, with the highest expression in the medial habenula. The modulation of GPR139 receptor function has been hypothesized to be beneficial in the treatment of some mental disorders, but behavioral studies have not yet provided causal evidence of the role of GPR139 in brain dysfunction. Because of the high expression of GPR139 in the habenula, a critical brain region in addiction, we hypothesized that GPR139 may play role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 60 publications
2
37
0
Order By: Relevance
“…Similarly, specific expression of GPR139 was observed, in agreement with rat and human expression patterns ( Liu et al, 2015 ) (75th and 168th most specific gene the lateral and medial habenula, respectively). A recent study demonstrated that activation of GPR139 reduces alcohol intake in alcohol-dependent rats ( Kononoff et al, 2018 ). Transient Receptor Potential Cation Channel Subfamily M Member 8 ( TRPM8 ), was highly expressed in both the lateral and medial habenula (ranked 3rd and 8th in the medial and lateral divisions, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, specific expression of GPR139 was observed, in agreement with rat and human expression patterns ( Liu et al, 2015 ) (75th and 168th most specific gene the lateral and medial habenula, respectively). A recent study demonstrated that activation of GPR139 reduces alcohol intake in alcohol-dependent rats ( Kononoff et al, 2018 ). Transient Receptor Potential Cation Channel Subfamily M Member 8 ( TRPM8 ), was highly expressed in both the lateral and medial habenula (ranked 3rd and 8th in the medial and lateral divisions, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical nociception, reflected by hindpaw withdrawal thresholds, was determined by an observer who was blind to the experimental groups using von Frey filaments that ranged from 3.63 to 281.838 g as previously reported (Dixon, 1965;Kononoff et al, 2018). A test session began after 10 min of habituation to the testing environment immediately following the subcutaneous injection of naloxone (WD, WD1ABX, and SAL groups) or saline (OXY and OXY1ABX groups).…”
Section: Mechanical Nociceptive Von Frey Testmentioning
confidence: 99%
“…Glutamatergic neurotransmission and hyperexcitability of the LHb is manifest during withdrawal, and this process appears to be driven by enhanced functions of TRPV1 vanilloid receptors (Gregor et al, ) and suppression of M‐type potassium channels (Kang et al, ). One viable therapeutic target in the LHb‐mediating AUD symptoms is the orphan G protein–coupled receptor GPR139 (Kononoff et al, ). Antagonism of GPR139 with JNJ‐63533054 reduced both escalated drinking and hyperalgesia symptoms in alcohol‐dependent rats.…”
Section: Preclinical Findings In Rodent Models Of Alcohol Dependence mentioning
confidence: 99%